The Effectiveness of Electronic Land Title Certificate Checking Services in Helping PPAT Perform Their Job Duties - Wahid, Muhammad Luqman (Sultan Agung Notary Law Review, 2023)
This research aims to determine and analyze the effectiveness of the implementation of electronic certificate checking services for the PPAT of Sragen Regency, and to find out the constraints and obstacles experienced by the PPAT and to find out the legal strength of the electronic checking results as a basis for making deeds for the PPAT. The research approach used in this thesis is an empirical or juridical legal research method. This research specification uses empirical juridical research methods or field research. The types of data used in this research are primary data and secondary data. The data analysis method is by collecting research materials and then analyzing them using description techniques. The results of the research show that the effectiveness of the certificate checking service for PPAT Sragen Regency in assisting their duties and positions is currently not fully effective because there are still several obstacles and obstacles. The results of checking the certificate electronically have legal force and are valid evidence in accordance with the procedural law in force in Indonesia.